Investigation on the surface treatments of CdMnTe single crystals. (March 2015) - Shen, Min; Zhang, Jijun; Wang, Linjun; Min, Jiahua; Wang, Lin; Liang, Xiaoyan; Huang, Jian; Tang, Ke; Liang, Wei; Meng, Hua
Abstract: The surface quality of CdMnTe crystal plays an important role in the performance of CdMnTe nuclear radiation detectors. In this paper, the surfaces of CdMnTe samples treated by Mechanical Polishing (MP), Chemical Polishing (CP), Chemical–Mechanical Polishing (CMP), and CMP followed by CP treatment (CMP+CP) were investigated. The structural properties of CdMnTe surfaces were characterized by a High Resolution Scanning Electron Microscope (HRSEM), Atomic Force Microscopy (AFM) and X-ray Photoelectron Spectroscopy (XPS). The Circular Transmission Line Model (CTLM) was adopted to reveal the specific contact resistivity ( ρ c ) of Au/CdMnTe contacts after various surface treatments. The AFM measurements shown an ultra-smooth surface was achieved after the CMP+CP treatment with the roughness value of 0.84 nm, and the surfaces by MP, CP and CMP were with the roughness of 8.2 nm, 5.1 nm and 1.4 nm, respectively. The XPS analysis indicated that the (Te+Te 4+ )/(Cd+Mn) ratios of the CdMnTe samples after the CMP+CP and MP treatment were 1.1 and 1.07 which are close to stoichiometric composition, while after the CP and CMP treatment were 2.00 and 1.40 which are enriched with Te. The CMP+CP treatment decreased the Te 4+ /(Te+Te 4+ ) ratio from 7% in CMP to 1%, which reveals the surface with few Te oxides. The specific contact resistivity ( ρ c ) was used to determine the ohmic characteristic of Au/CdMnTe contacts by the CTLM. The calculated ρ c values of Au/CdMnTe contacts on the CP, CMP and CMP+CP treated surfaces are 383, 112 and 15 Ω cm 2, respectively.